A Custom DNA-Based NGS Panel for the Molecular Characterization of Patients With Diffuse Gliomas: Diagnostic and Therapeutic Applications - Tirrò, Elena; Massimino, Michele; Broggi, Giuseppe; Romano, Chiara; Minasi, Simone; Gianno, Francesca; Antonelli, Manila; Motta, Gianmarco; Certo, Francesco; Altieri, Roberto; Manzella, Livia; Caltabiano, Rosario; et al. (Frontiers in Oncology, 2022)
The management of patients with Central Nervous System (CNS) malignancies relies on the appropriate classification of these tumors. Recently, the World Health Organization (WHO) has published new criteria underlining the importance of an accurate molecular characterization of CNS malignancies, in order to integrate the information generated by histology. Next generation sequencing (NGS) allows single step sequencing of multiple genes, generating a comprehensive and specific mutational profile of the tumor tissue. We developed a custom NGS-based multi-gene panel (Glio-DNA panel) for the identification of the correct glioma oncotype and the detection of its essential molecular aberrations. Specifically, the Glio-DNA panel targets specific genetic and chromosomal alterations involving ATRX chromatin remodeler (ATRX), cyclin dependent kinase inhibitor 2A (CDKN2A), isocitrate dehydrogenase (NADP+) 1 (IDH1) and the telomerase reverse transcriptase (TERT) promoter while also recognizing the co-deletion of 1p/19q, loss of chromosome 10 and gain of chromosome 7. Furthermore, the Glio-DNA panel also evaluates the methylation level of the O-6-methylguanine-DNA methyltransferase (MGMT) gene promoter that predicts temozolomide efficacy. As knowledge of the mutational landscape of each glioma is mandatory to define a personalized therapeutic strategy, the Glio-DNA panel also identifies alterations involving "druggable" or "actionable" genes. To test the specificity of our panel, we used two reference mutated DNAs verifying that NGS allele frequency measurement was highly accurate and sensitive. Subsequently, we performed a comparative analysis between conventional techniques - such as immunohistochemistry or fluorescence in situ hybridization - and NGS on 60 diffuse glioma samples that had been previously characterized. The comparison between conventional testing and NGS showed high concordance, suggesting that the Glio-DNA panel may replace multiple time-consuming tests. Finally, the identification of alterations involving different actionable genes matches glioma patients with potential targeted therapies available through clinical trials. In conclusion, our analysis demonstrates NGS efficacy in simultaneously detecting different genetic alterations useful for the diagnosis, prognosis and treatment of adult patients with diffuse glioma.